Stages and Paths of Firm Internationalization: Testing the Value Chain Internationalization Framework - Curci, Roberto; Yagi, Noriko; Mackoy, Robert (Journal of Comparative International Management)

(untitled) (Management Futures, 2013)
The value chain internationalization framework allows us to describe and analyze firms’ stages and paths of internationalization. To test the framework validity and usefulness for categorizing stages of internationalization, we propose and test hypotheses based on metrics commonly used to measure the degree of internationalization of a firm (Sullivan, 1994). The framework is tested within the context of the internationalization processes of firms located in the greater Indianapolis area. Taking a location that people usually do not associate with global business, we are able to examine firms at all stages of internationalization. The results of the hypotheses tests suggest each framework category is associated with the hypothesized level of degree of internationalization. Therefore, our findings suggest the framework has validity and may be useful to practitioners and academicians to advance our understanding of this phenomenon.